(untitled) (Revista de Ciências Agroveterinárias, 2005)
The diversity of arbuscular mycorrhizal fungi (FMAs) have the potential to influence plant growth and fungi community interactions. The aim of this work was to estimate the influence of covering plant on FMAs during and after maize cultivation. Samples of soil were collected in Covering Plant Soil Trial, at Experimental area in Soil Department- UFSM/RS. The species Canavalia ensiformes promoted higher number of spores population of FMAs than the other covering plant species used in the trail. The genera Acaulospora, Glomus e Scutellospora were detected in the experimental area. The higher diversity of FMAs was observed in areas without cultivation and when Crotalaria juncea was grown.